Situacion de la habichuela en el Valle del Cauca - Palacios V., Y.; Agudelo O., O. (International Center for Tropical Agriculture, 1987)
Aspects of snap bean cultivation in Valle del Cauca (Colombia) are analyzed. They include importance, area, cultivation systems, irrigation, planting times, seed, var., herbicides, diseases and pests and their control, crop rotation, fertilization, harvest, quality standards for purchasing, genetic improvement, production costs, and income. Snap bean production is for inner consumption. Economic parameters such as profit, unitary cost, and break even point show the great advantages of growing snap beans in winter, mainly due to the water demand of the crop. (CIAT)